Denmark 2023 - Connolly, Sean; Elliott, Mark; Nielsen, Adrienne Murray; O'Malley, Thomas (Lifestyle writer) (Lonely Planet guides., 2023)
Lonely Planet's Denmark is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Dine in innovative restaurants in Copenhagen, learn about Denmark's Viking past and relax on artistic Bornholm island's beaches; all with your trusted travel companion.